Melanoma of Urinary Bladder presented as acute urine retention - Lamichhane, Nirmal; Dhakal, Hari P. (Nepalese Journal of Cancer, 2017)
This report is of a 50-year-old man with a rare urinary bladder melanoma. He presented with hematuria followed by bladder outlet obstruction at the time of presentation. Ultrasonogram of the pelvis revealed a mass in the bladder outlet, suggestive of enlarged prostate. Suprapubic cystostomy was then performed. Subsequent transvesical exploration revealed a dark coloured mass at the outlet of bladder, which on histopathology confirmed to be melanoma. After ruling out other possible primary sites, he underwent radical cysto-urethrectomy with urinary diversion. Disease was confirmed with immunohistochemistry. Patient died after 3 months with bilateral lung metastasis.